Associations between self-reported impulsivity and a latent variable of impulsive action constructed from three laboratory tasks. Issue 3 (15th July 2019) - Hasegawa, Akira; Somatori, Keita; Nishimura, Haruki; Hattori, Yosuke; Kunisato, Yoshihiko
Previous research on relationships between self-reported impulsivity and behavioral impulsivity has been limited because behavioral impulsivity was assessed using individual tasks. To alleviate the task-impurity problem and the low reliability of laboratory tasks assessing impulsivity, the present study examined the correlations between a latent variable constructed from the performances of three laboratory tasks assessing impulsive action and each dimension of self-reported impulsivity. University students in Japan ( N = 176) responded to the UPPS-P Impulsive Behavior Scale assessing five dimensions of self-reported impulsivity that included the following: negative urgency, lack of premeditation, lack of perseverance, sensation seeking, and positive urgency. They also conducted laboratory tasks for assessing impulsive action: the go/no-go task, stop signal task, and Conners continuous performance test 3rd edition (CCPT). Results indicated weak correlations between each dimension of self-reported impulsivity and the latent variable named impulsive action constructed from the performances of three laboratory tasks (mean r = .10) and with the performances of individual laboratory tasks (mean r = .03). The latent variable of impulsive action and the commission error rate in the CCPT were significantly correlated with sensation seeking. However, this association disappeared after controlling for the influence of gender. These findings suggested that measures of self-reported and behavioral impulsivity might assess different constructs.